Comparison of the tumor microenvironments of squamous cell carcinoma at different anatomical locations within the upper aerodigestive tract in relation to response to ICI therapy. Issue 1 (10th January 2022) - van Duijvenvoorde, Maurice; Derks, Sarah; Bahce, Idris; Leemans, C René; van de Ven, Rieneke; Fransen, Marieke F
Abstract: Immunotherapy with immune checkpoint inhibitors (ICI) has improved treatment outcomes in many cancer types and has focused attention on cancer immunity and the role of the tumor microenvironment (TME). Studies into efficacy of immunotherapy and TME are generally restricted to tumors in one anatomical location, while the histological type may have substantial influence on the contexture of the TME, perhaps more so than anatomical location, and subsequently to the response to immunotherapy. This review aims to focus on the TME in ICI‐treated tumors of the same histological type, namely carcinogen‐induced squamous cell carcinoma developing within the aerodigestive tract, at three locations, i.e. head and neck (HNSCC), esophagus (ESCC) and lung (LUSC). Abstract : In this review, we focus on the tumor microenvironment in immune checkpoint inhibitor (ICI)–treated tumors of the same histological type, namely carcinogen‐induced squamous cell carcinoma developing within the aerodigestive tract, at three locations, i.e. head and neck, esophageal, and lung squamous cell carcinoma (SCC). We conclude, based on the available literature, that there are many similarities among SCC arising in distinct anatomical locations. However, the differences observed in immune landscapes, in the future, ICI treatments (and other immunotherapeutics) are probably best chosen based on immune cell infiltrate.